2006
DOI: 10.1242/jeb.02164
|View full text |Cite
|
Sign up to set email alerts
|

Odours detected by rhinophores mediate orientation to flow in the nudibranch mollusc,Tritonia diomedea

Abstract: SUMMARY Tritonia diomedea is a useful neuroethological model system that can contribute to our understanding of the neural control of navigation. Prior work on both sensory and locomotory systems is complemented by recent field experiments, which concluded that these animals primarily use a combination of odours and water flow as guidance cues. We corroborate these field results by showing similar navigation behaviours in a flow tank. Slugs crawled upstream towards both prey and conspecifics, an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
34
0

Year Published

2007
2007
2020
2020

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 39 publications
(36 citation statements)
references
References 45 publications
2
34
0
Order By: Relevance
“…The lack of any obvious olfactory glomeruli in Archidoris may indicate that the rhinophore may not serve in the Wrst line as an olfactory organ for long distance reception of odorants and may be a primarily tactile or rheotaxic organ. In favour of the rhinophores as an olfactory organ Wyeth and Willows (2006) showed the importance of predator or prey odour plumes for navigational response in Tritonia. Receptor neurons within the rhinophore epithelium of Archidoris may not be very sensitive to stimulation with amino acids.…”
Section: Discussionmentioning
confidence: 99%
“…The lack of any obvious olfactory glomeruli in Archidoris may indicate that the rhinophore may not serve in the Wrst line as an olfactory organ for long distance reception of odorants and may be a primarily tactile or rheotaxic organ. In favour of the rhinophores as an olfactory organ Wyeth and Willows (2006) showed the importance of predator or prey odour plumes for navigational response in Tritonia. Receptor neurons within the rhinophore epithelium of Archidoris may not be very sensitive to stimulation with amino acids.…”
Section: Discussionmentioning
confidence: 99%
“…The specialist nudibranch Tritonia diomedea used watersoluble cues in flow to move toward its prey and toward conspecifics in laboratory experiments (Wyeth and Willows, 2006b). In Y-maze experiments, T. diomedea consistently moved toward chemical cues, but the chemotaxis response was eliminated with the removal of rhinophores, the major olfactory organ in opisthobranchs (Chase, 2002).…”
Section: Consumer Neuroecologymentioning
confidence: 99%
“…In Y-maze experiments, T. diomedea consistently moved toward chemical cues, but the chemotaxis response was eliminated with the removal of rhinophores, the major olfactory organ in opisthobranchs (Chase, 2002). Using an en passant suction electrode to measure action potentials from neurons in rhinophores isolated from T. diomedea, Wyeth and Willows (2006b) detected significant increases in the number and frequency of action potentials associated with waterborne cues from prey, predator, and conspecific individuals. These experiments also indicated that physical properties such as flow affect the ability of T. diomedea to use olfaction to detect prey and conspecifics in the laboratory (Wyeth and Willows, 2006b), and video analysis demonstrated that water flow affects chemotaxis similarly in the field (Wyeth and Willows, 2006a).…”
Section: Consumer Neuroecologymentioning
confidence: 99%
See 1 more Smart Citation
“…By contrast, aquatic gastropods also often have a primary reliance on odour-based navigation (Croll, 1983;Cummins and Wyeth, 2014), yet have more narrowly spaced sensory structures and a lower typical speed of locomotion that might lead to differences in navigation adaptations when compared with the faster taxa. Our objective then was to build on recent efforts (Ferner and Weissburg, 2005;Wilson and Weissburg, 2012;Wyeth and Willows, 2006b;Wyeth et al, 2006) to explore the navigational strategies used by gastropods in turbulent odour plumes. A parallel motivation was to isolate the sensory structures that contribute to odour-based navigation in the nudibranch Tritonia diomedea (Bergh 1894) (synonymous with Tritonia tetraquetra; Martynov, 2006).…”
Section: Introductionmentioning
confidence: 99%